SERUM LL-37, GALECTIN-3, AND TOLL-LIKE RECEPTORS-3 LEVELS DECREASE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Karatas, A.; Akkoc, R. F.; Koca, S. S. (Elsevier, 2020)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 03, 2020 -- ELECTR NETWORK